Transitioning from harmful insecticides to agroecological IPM with smallholder vegetable farmers in Ethiopia - Williamson, Stephanie; Belay, Atalo; Mensah, Robert; Genet, Zemenu; Kabero, Gemeda; Nigussie, Asaminew; Amera, Tadesse; Horgan, Finbarr G.; Willis, Sheila E.; Salmon, Joey P.; Stuart, Alexander M. (Frontiers in Agronomy, 2025)
Lake Ziway in Ethiopia’s Central Rift Valley is an important region for vegetable production. Intensive pesticide use in the region has resulted in declining health and negative impacts on the environment. This case study reports on a project to reduce the impacts of pesticide use in smallholder vegetable production. We used Farmer Field School (FFS) training with agroecological integrated pest management (IPM) group learning plots of onion and tomato to help farmers and other stakeholders to transition to safer pest management alternatives. Learning plots were adaptively managed with updated information directly incorporated into stakeholder training. Furthermore, the project adapted for vegetable production a successful biocontrol enhancement method that used vegetation strips as a form of habitat manipulation and locally sourced natural enemy food spray attractants. The project trained over 700 farmers in season-long training and a further 500 via peer mentoring. The final impact survey on trained farmers’ changes in pest management found an average 73% reduction in insecticide application frequency compared to before training. Applications of organophosphates were reduced by 96%, and 70% of respondents had eliminated their use. 85% of surveyed farmers reported they now apply food spray and sow habitat strips of alfalfa or maize, while 60% of farmers reported they avoid insecticides harmful to natural enemies. Furthermore, the self-reported yearly incidence rate of acute pesticide poisoning reduced from 20% of farmers surveyed in the baseline survey to 5.5% in the endline survey, without adversely affecting yields or profits, often with positive gains. The project demonstrates that, by adopting an agroecological approach, economically sustainable vegetable production can be achieved while greatly reducing the pesticide footprint. Our experience also shows how successful technologies developed for one crop can be transferred to other crops (i.e. onion and tomato) through the active participation and support of end-use stakeholders.